RESULTS OF CZECH NATIONAL STUDY OF RADIATION EXPOSURE FROM RADIOTHERAPY OF NON-MALIGNANT DISEASES, IN PARTICULAR OF HEEL SPURS - Dufek, V; Zackova, H; Kotik, L; Horakova, I (Radiation protection dosimetry, 2019)
About 26 000 patients are treated per year with radiotherapy for non-malignant diseases in the Czech Republic. Approximately 75% of them are treated on X-ray therapy units and most of these patients undergo radiotherapy of heel spurs. The evaluation of radiation exposure of these patients was based on measured organ doses and on data from clinical practice. Collective effective doses for particular diagnoses were calculated in order to compare doses resulting from different diagnoses treated on X-ray therapy units. The collective effective dose from radiotherapy of heel spurs in the Czech Republic in 2013 was evaluated to 77 manSv. It represents 25.6% of the total collective effective dose for all diagnoses of radiotherapy for non-malignant diseases treated on X-ray therapy units.
Keywords: X-Ray Therapy; kritické orgány; ostruha kosti patní; Humans; Radiotherapy Planning, Computer-Assisted; Phantoms, Imaging; monitorování radiace; Radiotherapy Dosage; Radiation Monitoring; Organs at Risk; celková dávka radioterapie; lidé; Heel Spur; Male; plánování radioterapie pomocí počítače; Czech Republic; radiační expozice; Radiation Exposure; Česká republika; mužské pohlaví; fantomy radiodiagnostické; rentgenová terapie